Investigação fitoquímica de Cordia trichotoma (Vell.) Arráb. ex Steud. (Boraginaceae) - Lins, Jociano da Silva (2021)
The Boraginaceae family comprises about 130 genera and 2,300 species, with a cosmopolitan distribution. In Brazil, the family is represented by 9 genera and approximately 129 species, with the genera Cordia, Heliotropium and Tournefortia being the most numerous. The species Cordia trichotoma (Vell.) Arráb. ex Steud has a wide distribution in tropical and subtropical regions. In Brazil, it is popularly known as the laurel-brown, being widely distributed in the Brazilian territory, from the northeast to the south of the country. Brown laurel leaf tea is used in folk medicine to treat rheumatism, arthritis, rickets, kidney disease, flu, cold and fever. Therefore, this work aims to contribute to the phytochemical knowledge of the Boraginaceae family through the isolation of secondary metabolites from the aerial parts of C. trichotoma. To carry out this work, the leaves and branches of C. trichotoma were collected in the municipality of Matureia-PB, and were subjected to processes of drying, spraying, extraction and chromatographic techniques for the isolation of its chemical constituents. The chemical structures of the isolated substances were identified through the analysis of 1H and 13C oneand two-dimensional nuclear magnetic resonance data, infrared and by comparisons with the literature. In this study, nine substances were isolated: 2-hydroxybenzeneacetonitrile, reported for the first time as a natural plant product; a mixture of 4-hydroxybenzeneacetonitrile and phydroxybenzoic acid, isolated for the first time in the family and species, respectively; Ecoclauril and ethyl caffeate, reported for the first time in family and genus, respectively; ethyl3,4-dihydroxyphenylacetate, reported for the first time in the species. In addition to these, the compounds caffeic acid, rosmarinic acid and p-hydroxybenzoic acid were re-isolated. These results contributed to the chemical knowledge of the Boraginaceae family, through the phytochemical study of C. trichotoma that resulted in the isolation of new compounds in this species.